Deep Red Emissive Carbonized Polymer Dots with Unprecedented Narrow Full Width at Half Maximum - Liu, Junjun (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.